Analisis Yuridis Perlindungan Konsumen Dalam Produk Halal Berdasarkan UU No 33 Tahun 2014 Tentang Jaminan Produk Halal (Studi Pada Lembaga Pembela Konsumen Negeri) - Lubis, Andi Nursin; Ahmad, Akiruddin; Sahbudi, Sahbudi (Universitas Medan Area, 2025)
This research focuses on a legal analysis of consumer protection in halal products based on Law No. 33 of 2014 concerning Halal Product Assurance (UU JPH), with the study locus at the State Consumer Defense Institute (LPKN). The problems studied cover three main aspects, namely: legal regulations regarding halal product assurance in Indonesia, normative weaknesses still inherent in the JPH Law, and obstacles faced by LPKN in protecting consumers in dispute resolution. The research methodology uses a normative and empirical legal approach supported by a statute approach and literature study. Data sources consist of primary legal materials in the form of laws and regulations, secondary legal materials in the form of literature and scientific works, and tertiary legal materials functioning as supporting analysis. The analysis technique is carried out qualitatively with grammatical, systematic, and historical interpretations, resulting in the construction of comprehensive legal arguments. The research findings indicate that the JPH Law stipulates the obligation of halal certification for all products circulating in Indonesia, with the technical implementation function being held by the Halal Product Assurance Organizing Agency (BPJPH) and the authority to issue fatwas being delegated to the Indonesian Ulema Council (MUI). The results of this study emphasize the importance of strengthening a more transparent halal product assurance system, decentralizing authority in the certification process, and increasing the capacity of consumer protection agencies. Public education regarding the significance of halal certification also needs to be promoted to strengthen Muslim consumer protection and ensure legal certainty in trade practices.